Design of a participatory blended learning model in partnership with schools and parents of elementary school students - Deni Hardianto; Unik Ambar Wati (Jurnal Inovasi Teknologi Pendidikan, 2022)
Desain model pembelajaran untuk membangun kemitraan sekolah dan orang tua siswa belum banyak dikembangkan, sementara dalam banyak literatur ditemukan bahwa partisipasi orang tua dalam proses pendidikan di sekolah sangat berpengaruh pada hasil belajar siswa. Penelitian ini bertujuan menghasilkan desain model pembelajaran blended-partisipatif kemitraan sekolah dan orang tua siswa SD yang layak dan praktis untuk diterapkan. Metode penelitian dan pengembangan yang digunakan untuk menghasilkan desain model pembelajaran yaitu metode pengembangan model ADDIE. Teknik pengumpulan data menggunakan angket, sedangkan analisis data menggunakan analisis deskriptif-kuantitatif. Hasil pengembangan tersusun model pembelajaran blended-partisipatif kemitraan sekolah dan orang tua siswa SD yang layak dan praktis berdasarkan hasil validasi pakar dengan skor rerata 3.50. Penilaian pakar materi kemitraan sekolah dan orang tua yaitu 3,79 atau sangat layak sementara penilaian pakar pembelajaran terhadap desain model pembelajaran blended mendapat skor 3.81 atau sangat layak untuk diimplementasikan. Hasil uji kepraktisan yaitu diperoleh skor 3,64 atau sangat layak. Rekomendasi penelitian ini berupa penerapan desain model ini di seluruh sekolah dasar dengan karakteristik sekolah yang relevan.The design of learning models to build school partnerships with students' parents has yet to be widely developed. At the same time, in a lot of literature, it is found that parental participation in the educational process in schools greatly influences student learning outcomes. This study aims to design a participatory blended learning model in partnership between schools and parents of elementary school students that is feasible and practical to implement. The research and development method used to produce a learning model design is the ADDIE model development method. Data collection techniques use questionnaires, while data analysis uses descriptive-quantitative analysis. The development results are a decent and practical blended-participatory learning model based on the results of expert validation with an average score of 3.50. The material expert's assessment of school partnerships and parents was 3.79 or very feasible. In contrast, the learning expert's evaluation of the blended learning model design received a score of 3.81, or very viable to implement. The practicality test results obtained a score of 3.64 or very feasible. The recommendation of this research is the implementation of this model design in all elementary schools with relevant school characteristics.